Mother, Mother I want another - Robbins, Maria Polushkin; Goodell, Jon (New York : Knopf : Distributed by Random House, 2005)
In this newly illustrated edition, Mrs. Mouse is anxious to get her son to sleep and goes off to find what she thinks he wants
Keywords: Mice -- Fiction; Sleep -- Fiction; Bedtime -- Fiction